2013
DOI: 10.1016/j.lindif.2013.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Academic buoyancy and psychological risk: Exploring reciprocal relationships

Abstract: Based on hypothesized reciprocal relations between psychological risk and academic buoyancy (dealing with 'everyday' academic setback in the ordinary course of school life), the present study used cross-lagged structural equation models to examine the relative salience of (1) prior academic buoyancy in predicting subsequent psychological risk and (2) prior psychological risk in predicting subsequent academic buoyancy. Academic buoyancy and psychological risk (academic anxiety, failure avoidance, uncertain cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 32 publications
(44 reference statements)
1
63
0
3
Order By: Relevance
“…The finding of reciprocal relations between worry and buoyancy supports previous findings in the context of general academic anxiety (Martin & Marsh, ,b; Martin et al ., , ). The statistically significant cross‐lagged paths from worry to academic buoyancy support the theorizing of Putwain and Daly () that academic buoyancy can impact on self‐regulative thought to influence the appraisal of a high‐stakes examination as more or less threatening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding of reciprocal relations between worry and buoyancy supports previous findings in the context of general academic anxiety (Martin & Marsh, ,b; Martin et al ., , ). The statistically significant cross‐lagged paths from worry to academic buoyancy support the theorizing of Putwain and Daly () that academic buoyancy can impact on self‐regulative thought to influence the appraisal of a high‐stakes examination as more or less threatening.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of this model, Putwain and Daly (2013) proposed that academic buoyancy can protect against the appraisal of a performance-evaluative situation as threatening. Academically buoyant students are able to draw on positive self-beliefs (e.g., competence beliefs and motivation) and to respond to lower-than anticipated marks or grades on schoolwork and examinations with effort and strategic attributions (see Malmberg et al, 2013;Martin, 2013;Martin et al, 2010Martin et al, , 2013Martin & Marsh, 2006, 2008a. Academic buoyancy would be expected to impact on key self-regulative mechanisms, as proposed by Zeidner and Matthews (2005), to reduce the appraisal of performance-evaluative situations as threatening and result in lower test anxiety.…”
Section: Relations Between Test Anxiety and Academic Buoyancymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the work of Skinner and her colleagues (see Skinner & Pitzer, 2012) provided a systematic analysis of students' academic coping behaviors and suggests that the same characteristics that enable engagement (e.g., feelings of competence) also inform responses to setbacks or challenges. Using data from a large-scale survey, Martin, Ginns, Brackett, Malmberg, and Hall (2013) reported on the reciprocity of resilience or buoyancy and psychological risk factors such as academic anxieties, need for control, emotional instability, and failure avoidance. Finally, Turner, Warzon, and Christensen (2011) suggested that promoting teacher understanding of student motivation can lead to positive changes in instructional practice, thereby positively impacting student engagement.…”
mentioning
confidence: 99%
“…Despite the demonstrated positive effects of buoyancy on motivational and emotional factors (e.g., Martin et al, 2013), a question remains concerning achievement. Martin (2014) examined a direct relationship between buoyancy and achievement and found a significant association; however, effect sizes were generally small.…”
mentioning
confidence: 99%